2016
DOI: 10.1097/cmr.0000000000000255
|View full text |Cite
|
Sign up to set email alerts
|

Skin self-examination and long-term melanoma survival

Abstract: To evaluate the effect of skin self-examination (SSE) on melanoma mortality, we estimated the survival for individuals performing SSE compared with those who did not. Participants were from a previously carried out case-control study, who were newly diagnosed melanoma cases in 1987-1989. A 20-year survival analysis was carried out using death (event) and other causes of death (competing). Cumulative incidence functions were evaluated using Gray's test and proportional subdistribution hazards regression models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 34 publications
0
44
0
Order By: Relevance
“…A comprehensive population‐based study of risk factors for incidence and mortality of cutaneous melanoma in Connecticut was conducted between 1986–1987 (incidence) and 2007 (mortality) (Berwick, Begg, Fine, Roush, & Barnhill, ; Paddock et al, ). Of the 650 individuals newly diagnosed with a first primary melanoma of Northern European ancestry in this study, 280 individuals died of any cause, and 123, or 19%, had died of melanoma at the end of follow‐up on July 1, 2007.…”
Section: Methodsmentioning
confidence: 99%
“…A comprehensive population‐based study of risk factors for incidence and mortality of cutaneous melanoma in Connecticut was conducted between 1986–1987 (incidence) and 2007 (mortality) (Berwick, Begg, Fine, Roush, & Barnhill, ; Paddock et al, ). Of the 650 individuals newly diagnosed with a first primary melanoma of Northern European ancestry in this study, 280 individuals died of any cause, and 123, or 19%, had died of melanoma at the end of follow‐up on July 1, 2007.…”
Section: Methodsmentioning
confidence: 99%
“…There is US trial evidence for the efficacy of SSE skills training and reminders among patients recently diagnosed with melanoma 37 and among skin clinic patients without melanoma. 38 Furthermore, the Check It Out randomized clinical trial, set in the United States among a similar population with increased risk of melanoma, reported that increasing SSE practices in the short-term resulted in more abnormal lesions detected and more skin surgical procedures, 39 although, like our trial, it was not powered to detect melanoma diagnosis. In the United States, most studies have been set among people previously treated for a melanoma and, therefore, with very high risk for development of a new primary melanoma as well as recurrence.…”
Section: Discussionmentioning
confidence: 76%
“…One case–control study in the late 1980s found short‐term mortality benefits for people diagnosed with melanoma who conducted skin self‐examination . However, at 20‐year follow‐up, taking into account competing risks, the effect was no longer significant …”
mentioning
confidence: 99%
“…6 However, at 20-year follow-up, taking into account competing risks, the effect was no longer significant. 7 Digital technology may now allow a quantum shift in evidence generation. For example, people could be asked to send photographs of specific spots or moles a clinician recommended to monitor, or could take photos of body regions that are common locations for melanoma (back, or back of the neck in men; lower legs in women).…”
mentioning
confidence: 99%